Being privileged but challenged: Understanding Chinese international students’ college choice process - Wu, Fanya; Liu, Ren (Journal of International Students, 2025)
This study explores how Chinese international students at a state university navigate the U.S. college choice process. Through semi-structured interviews with 10 Chinese international college students at a large public research university located in the northeastern U.S., this study explains how these economically privileged students regard studying abroad as a “Plan B” substituting Gaokao (the Chinese College Entrance Examinations) and as an opportunity to access high-quality higher education. This study argues that these economically privileged students are challenged while navigating the college choice process because of the lack of cultural support from parents and private agents and the lack of connection with the college community before arriving in the U.S. This study sheds light on international students’ college choice process and this group of students’ specific needs at each stage. This study suggests that institutions outreach prospective international students by holding summer camps or virtual open-house opportunities.